Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 10th ACM Workshop on Hot Topics in Networks 2011
DOI: 10.1145/2070562.2070583
|View full text |Cite
|
Sign up to set email alerts
|

The middlebox manifesto

Abstract: Most network deployments respond to changing application, workload, and policy requirements via the deployment of specialized network appliances or "middleboxes". Despite the critical role that middleboxes play in introducing new network functionality, they have been surprisingly ignored in recent efforts for designing networks that are amenable to innovation. We make the case that enabling innovation in middleboxes is at least as important, if not more important, as that for traditional switches and routers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(22 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Moreover, policy changes or the addition of new functionalities to a network usually requires additional MBs. As reported in , in a network with 80K users, the total number of MBs is to some extent of the order of the number of switching elements.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, policy changes or the addition of new functionalities to a network usually requires additional MBs. As reported in , in a network with 80K users, the total number of MBs is to some extent of the order of the number of switching elements.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies indicate that various kinds of policy chains are in use in different networks . These chains can be called service function chains (SFCs) .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many proposals in the literature for programmable middlebox platforms [50,51]. However, since those boxes have very different functions, it can be difficult to define a unique set of control APIs.…”
Section: B Existing Programmable Architecturesmentioning
confidence: 99%
“…Research [ 2] shows that the number of middleboxes is on par with the number of routers in enterprise networks, such as an average very large network that hosts about 2,850 Layer 3 routers and 1,946 total middleboxes. Furthermore, it is reported that the market for network security appliances alone is estimated to rise to ten billion in 2016 [3]. So it is believed that the number of middleboxes as a critical part of today's networks will be on rapid growth in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%